KOMUNIKASI EFEKTIF PUBLIC RELATIONS DALAM MENINGKATKAN KINERJA DAN PELAYANAN PRIMA - Utama Putra, I Putu Gede Untung; Jelantik, Sayu Kadek; Adnyana, Ida Bagus Dirga Wira (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Public relations communication is a communication tool between an institution and the community. Public relations communication activities are carried out by public relations officers who are in charge of distributing information and services to the public. The purpose of the article is to analyze the effectiveness of public relations communication at the Office of the Ministry of Religion of West Lombok Regency. Using mathematical theory to answer supporting and inhibiting factors. This research uses a descriptive qualitative approach with the research subject on public relations communication activities at the West Lombok Regency Ministry of Religion office. Primary data is in the form of information data from public relations members and the fostered community in the West Lombok Regency area. Data collection techniques using observation, interviews, and documentation techniques. The results show that the effectiveness of public relations communication in excellent service to the community in West Lombok Regency consists of human resources that are still lacking in the public relations team, a digital information system that has not been maximized, and a programmed information system and community services in the public relations team. Supporting factors include information services and community development in collaboration with the Hindu and Islamic Bimas sub-units, support for access to information on the kemenagntb.com website, the availability of sufficient budget to fund the public relations work system in community services.